Analysis of Village Apparatus Performance in Providing Public Services to the Community Based on Law No. 25 of 2009: (Study at the Sungai Purun Kecil Village Office, Mempawah Regency) - Muhammad Farizki (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the performance of village officials in providing public services to the community in Sungai Purun Kecil Village, Sungai Pinyuh District, Mempawah Regency, based on Law Number 25 of 2009. The approach used was a normative qualitative approach with descriptive methods, collecting data through interviews, observation, and documentation. The results indicate that village officials have implemented administrative and social services in accordance with public service principles. However, there are obstacles in the aspects of information transparency, timeliness, and work discipline that affect the speed and quality of service. The human resource capacity of village officials also needs to be improved through training and competency development. This study recommends improving discipline, providing easily accessible information media, and increasing community participation in service performance evaluation as strategies to improve the quality of village public services. Thus, this research contributes to the development of effective and sustainable village public service governance.